1997
DOI: 10.1530/jrf.0.1090187
|View full text |Cite
|
Sign up to set email alerts
|

Induction of early pregnancy factor activity in vitro by platelet-activating factor in mice

Abstract: The rosette inhibition test was used to determine early pregnancy factor activity in culture media from oestrous mouse ovaries and oviducts stimulated in vitro for early pregnancy factor production under different experimental conditions. Embryo conditioned media, platelet-activating factor and cortical granule release media could all stimulate the production of early pregnancy factor by oestrous mouse ovaries and oviducts. This stimulation was completely blocked by the presence of BN 52021, a platelet-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…27 PAF initiates early pregnancy factor synthesis, which is recognized as an immunosuppressive factor and whose amount is highest on day 30 of pregnancy in gilts. 28,29 In this study, the improvement in pregnancy outcome induced by maternal NCG supply could be associated with the increase in serum PAF level. Collectively, alternations in levels of amniotic fluid and serum metabolites involved in energy metabolism, lipid metabolism, glutathione metabolism, and immunological regulation by maternal NCG supply were beneficial to embryonic development, which ultimately enhances pregnancy outcomes in sows.…”
Section: ■ Discussionmentioning
confidence: 67%
“…27 PAF initiates early pregnancy factor synthesis, which is recognized as an immunosuppressive factor and whose amount is highest on day 30 of pregnancy in gilts. 28,29 In this study, the improvement in pregnancy outcome induced by maternal NCG supply could be associated with the increase in serum PAF level. Collectively, alternations in levels of amniotic fluid and serum metabolites involved in energy metabolism, lipid metabolism, glutathione metabolism, and immunological regulation by maternal NCG supply were beneficial to embryonic development, which ultimately enhances pregnancy outcomes in sows.…”
Section: ■ Discussionmentioning
confidence: 67%
“…Furthermore, the increase in PAF receptors in the estrous ovaries supports the hypothesis that PAF is an important ovarian signaling mechanism. 7 On day 1 pc both ovarian and oviduct PAF receptors continue to be expressed which virtually disappear by day 4 pc in most tissue areas corresponding to the time of embryo entry into the uterus. Following implantation (day 7 pc in this work), blastocyst PAF increases 15 and ovarian PAF receptors increase but not in the oviduct.…”
Section: Discussionmentioning
confidence: 98%
“…Recently we proposed that PAF released by pre-implantation embryos was the factor by which early pregnancy factor synthesis was initiated by the ovary. 7 The objective of this study was to determine whether ovarian and oviduct PAF receptors corresponded to the time when embryo PAF synthesis was known to occur prior to implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have shown that when mouse estrous ovaries and oviducts are cultured with embryo conditioned media or platelet-activating factor (PAF) and prolactin, then EPF activity is detected in the culture media (11). This system could provide the basis to identify the identity of EPF directly using both protein microchemistry and molecular biology techniques.…”
Section: Early Pregnancy Factor: An Unresolved Moleculementioning
confidence: 99%